Can chronic stretching change the muscle‐tendon mechanical properties? A review - Freitas, S. R.; Mendes, B.; Le Sant, G.; Andrade, R. J.; Nordez, A.; Milanovic, Z. (Scandinavian journal of medicine & science in sports, 2018)
It is recognized that stretching is an effective method to chronically increase the joint range of motion. However, the effects of stretching training on the muscle‐tendon structural properties remain unclear. This systematic review with meta‐analysis aimed to determine whether chronic stretching alter the muscle‐tendon structural properties. Published papers regarding longitudinal stretching (static, dynamic and/or PNF) intervention (either randomized or not) in humans of any age and health status, with more than 2 weeks in duration and at least 2 sessions per week, were searched in PubMed, PEDro, ScienceDirect and ResearchGate databases. Structural or mechanical variables from joint (maximal tolerated passive torque or resistance to stretch) or muscle‐tendon unit (muscle architecture, stiffness, extensibility, shear modulus, volume, thickness, cross‐sectional area, and slack length) were extracted from those papers. A total of 26 studies were selected, with a duration ranging from 3 to 8 weeks, and an average total time under stretching of 1165 seconds per week. Small effects were seen for maximal tolerated passive torque, but trivial effects were seen for joint resistance to stretch, muscle architecture, muscle stiffness, and tendon stiffness. A large heterogeneity was seen for most of the variables. Stretching interventions with 3‐ to 8‐week duration do not seem to change either the muscle or the tendon properties, although it increases the extensibility and tolerance to a greater tensile force. Adaptations to chronic stretching protocols shorter than 8 weeks seem to mostly occur at a sensory level.